Answer:
First, plug-in x and y as 3sinθ-2 and 3cosθ+4 into the equation, respectively:
![((3\sin (\theta)-2)+2)^2 + ((3\cos (\theta)+4)-4)^2 = 9](https://img.qammunity.org/2021/formulas/mathematics/high-school/xsmyi9htvdlbh67bwbw0emwgf2qgk4b3r2.png)
Then, +2 and -2 cancel out and +4 and -4 cancel out as well, leaving you with:
![(3\sin(\theta))^2+(3\cos(\theta))^2=9](https://img.qammunity.org/2021/formulas/mathematics/high-school/6qx9rz55322nva023jp6zrdx2rqplc88ou.png)
We can factor out 3^2 = 9 from both equations:
![9(\sin(\theta)^2+cos(\theta)^2) = 9](https://img.qammunity.org/2021/formulas/mathematics/high-school/vs0hmxnufcovcvqypdcx33l2a21kx1o30c.png)
We know from a trigonometric identity that
, meaning we can reduce the equation to:
![9(1) = 9](https://img.qammunity.org/2021/formulas/mathematics/high-school/10s5d8w4s8nzod8yzpj6gjfkz3ilcwnbjk.png)
![9=9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iiqmwfdkliz2nft4gj3uwv6efljwen791g.png)
And therefore, we have shown that (x+2)^2 + (y-4)^2 = 9, if x=3sinθ-2 and y=3cosθ+4.
Hope this helped you.